BENZOTHIAZOLE: DIFFERENT METHODS OF SYNTHESIS AND DIVERSE BIOLOGICAL ACTIVITIES (International Journal of Pharmaceutical Sciences and Drug Research, 2011)
Substituted 1, 3-benzothiazole derivatives are an important class of heterocyclic compounds. In recent years heterocyclic compounds analogues and derivatives have attracted strong interest due to their biological and pharmacological properties. The benzothiazole nucleus containing compounds involved in research aimed at evaluating new products that possess biological activities, such as antimicrobial, anticancer, antifungal, anthelmintic, anti-diabetic, amyloid imagining agents and anticancer agents. The present review focus on the different methods of synthesis of substituted benzothiazoles with potential activities that are now in developing phase.